Effects of Antimalarial Drugs on Neuroinflammation-Potential Use for Treatment of COVID-19-Related Neurologic Complications - Wei-Yi Ong; Mei-Lin Go; De-Yun Wang; Irwin Kee-Mun Cheah; Barry Halliwell (Molecular Neurobiology, 2021)
The SARS-CoV-2 virus that is the cause of coronavirus disease 2019 (COVID-19) affects not only peripheral organs such as the lungs and blood vessels, but also the central nervous system (CNS)—as seen by effects on smell, taste, seizures, stroke, neuropathological findings and possibly, loss of control of respiration resulting in silent hypoxemia. COVID-19 induces an inflammatory response and, in severe cases, a cytokine storm that can damage the CNS. Antimalarials have unique properties that distinguish them from other anti-inflammatory drugs. (A) They are very lipophilic, which enhances their ability to cross the blood-brain barrier (BBB). Hence, they have the potential to act not only in the periphery but also in the CNS, and could be a useful addition to our limited armamentarium against the SARS-CoV-2 virus. (B) They are non-selective inhibitors of phospholipase A 2 isoforms, including cytosolic phospholipase A 2 (cPLA 2 ). The latter is not only activated by cytokines but itself generates arachidonic acid, which is metabolized by cyclooxygenase (COX) to pro-inflammatory eicosanoids. Free radicals are produced in this process, which can lead to oxidative damage to the CNS. There are at least 4 ways that antimalarials could be useful in combating COVID-19. (1) They inhibit PLA 2. (2) They are basic molecules capable of affecting the pH of lysosomes and inhibiting the activity of lysosomal enzymes. (3) They may affect the expression and Fe 2+ /H + symporter activity of iron transporters such as divalent metal transporter 1 (DMT1), hence reducing iron accumulation in tissues and iron-catalysed free radical formation. (4) They could affect viral replication. The latter may be related to their effect on inhibition of PLA 2 isoforms. Inhibition of cPLA 2 impairs an early step of coronavirus replication in cell culture. In addition, a secretory PLA 2 (sPLA 2 ) isoform, PLA2G2D, has been shown to be essential for the lethality of SARS-CoV in mice. It is important to take note of what ongoing clinical trials on chloroquine and hydroxychloroquine can eventually tell us about the use of antimalarials and other anti-inflammatory agents, not only for the treatment of COVID-19, but also for neurovascular disorders such as stroke and vascular dementia.

A transport environmental Kuznets curve analysis for Malaysia: exploring the role of corruption - You-How Go; Lin-Sea Lau; Feng-Mei Liew; Abdelhak Senadjki (Environmental Science and Pollution Research, 2021)

In-Silico Approaches to Multi-target Drug Discovery - Xiao Hua Ma; Zhe Shi; Chunyan Tan; Yuyang Jiang; Mei Lin Go; Boon Chuan Low; Yu Zong Chen (Pharmaceutical Research, 2010)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Upregulation of iron regulatory proteins and divalent metal transporter-1 isoforms in the rat hippocampus after kainate induced neuronal injury - En Huang; Wei-Yi Ong; Mei-Lin Go; James R. Connor (Experimental Brain Research, 2006)

Modulation of Digoxin Transport Across Caco-2 Cell Monolayers by Citrus Fruit Juices: Lime, Lemon, Grapefruit, and Pummelo - Jianguo Xu; Mei Lin Go; Lee-Yong Lim (Pharmaceutical Research, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)